2020
DOI: 10.1016/j.ijnss.2020.04.002
|View full text |Cite|
|
Sign up to set email alerts
|

A study on the psychological needs of nurses caring for patients with coronavirus disease 2019 from the perspective of the existence, relatedness, and growth theory

Abstract: a b s t r a c tObjective: This study aimed to explore the psychological needs of nurses caring for patients with coronavirus disease 2019 and to propose corresponding interventions. Methods: In-depth interviews were conducted with 10 nurses who cared for patients with COVID-19. Interview data were analyzed by category analysis from the perspective of the existence, relatedness, and growth theory (ERG). Results: The existence needs were mainly reflected in health and security needs, whereas the relatedness nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
171
2
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(224 citation statements)
references
References 1 publication
25
171
2
18
Order By: Relevance
“…[45] Good hospital guidance was identi ed to relief stress in a study by H.Cai et al [23], and increasing selfknowledge was a coping strategy deployed by staff. Dissemination of knowledge was also mentioned in a qualitative study by Yin & Zeng [42]; participants described subjective stress reduction after their seniors explained relevant knowledge to them.…”
Section: Occupational Factorsmentioning
confidence: 95%
See 4 more Smart Citations
“…[45] Good hospital guidance was identi ed to relief stress in a study by H.Cai et al [23], and increasing selfknowledge was a coping strategy deployed by staff. Dissemination of knowledge was also mentioned in a qualitative study by Yin & Zeng [42]; participants described subjective stress reduction after their seniors explained relevant knowledge to them.…”
Section: Occupational Factorsmentioning
confidence: 95%
“…This study also reported PPE as a protective factor. [42] Heavy Workload: Longer working time per week was found to be a risk factor in a study by Mo et al [33] This, together with increased work intensity or patient load per hour, were themes in a mixed methods study of 37 staff of a clinic in Beijing [25] and a qualitative study of nurses in China [35], also suggesting heavy workload as a risk factor.…”
Section: Occupational Factorsmentioning
confidence: 99%
See 3 more Smart Citations